Atomically smooth gallium nitride surface prepared by chemical-mechanical polishing with different abrasives. (October 2014) - Zou, Chunli; Pan, Guoshun; Shi, Xiaolei; Gong, Hua; Zhou, Yan
For chemical-mechanical polishing of epitaxial gallium nitride (GaN), a two-step experiment method with two kinds of abrasives, aluminum oxide (Al2 O3 ) and colloidal silica (SiO2 ), was put forward. The average material removal rates of GaN by the slurry with Al2 O3 and SiO2 abrasives were 594.79 and 66.88 nm/h, respectively. An atomically flat surface with roughness (Ra) of 0.056 nm was obtained after the second chemical-mechanical polishing process with SiO2 -based slurry, which presented an atomic step-terrace structure. The material removal characteristics of GaN surfaces were investigated in detail. A model was proposed to describe the different behaviors of the two kinds of abrasive during chemical-mechanical polishing process.